Professional development short scale: Measurement invariance, stability, and validity in Brazil and Angola - Mourão, Luciana; Tavares, Susana M.; Sandall, Hugo (Frontiers in Psychology, 2022)
Professional development is the vital process in the workplace that comprehend the growth and maturation of knowledge, skills, and attitudes acquired throughout life due to formal and informal actions of learning at work. The goal of the present research was to present validity evidence and accuracy of the Professional Development Short Scale (PDSS) for different occupational categories. This research consisted of four cross-sectional questionnaire surveys with convenience samples of different occupational categories (N = 2,547) in 41 cities in Brazil and Angola. The objective of the first study was to explore the factorial structure and internal consistency of the PDSS. The second study aimed to evaluate the cross-cultural validity and measurement invariance of the scale. The third study was to assess concurrent validity and predictive validity. The fourth study was to assess the test-retest reliability. The results indicated a one-factor structure, with four items for both countries' datasets. This research pointed out the validity of the PDSS as regards its convergence-discriminant pattern with the General Self-Efficacy and Job Self-Efficacy Scales. Also, the relationship of the PDSS with relevant constructs (Bases of Power/leadership styles, In-role performance, Job Satisfaction, Career Promotion). In this study, we provide psychometric validity of the Professional Development Short Scale to offer it as a resource to measure the construct and allow researchers to apply it in research models easily integrated to other constructs. We covered several different incremental approaches to ensure de scale validity. Besides showing temporal stability to ensure it can be applied from time to time as one dynamic construct should, we also indicated that social desirability did not influence the measurement of the PDSS. The results support the psychometric properties of the PDSS in that the scale is not unduly confounded with method effects. Thus, the psychometric properties of the PDSS are reasonably suitable for application in extensive studies. So, this scale contributes to the contemporary professional development literature by the comparison of the perceptions of professional development in different professional categories and by providing organizational researchers with a tool to evaluate the effects and predictors of such construct.